Home oxygen therapy for infants and young children with acute bronchiolitis and other lower respiratory tract infections: the HiTHOx program. (December 2013) - Zappia, Theresa; Peter, Sue; Hall, Graham; Vine, Julie; Martin, Andrew; Munns, Ailsa; Shields, Linda; Verheggenn, Maureen
<x xml:space="preserve">Abstract</x> Background: Acute lower respiratory tract infection (LRTI) including bronchiolitis, is one of the leading causes of pediatric hospital admissions worldwide. Recent studies have demonstrated that some children with acute bronchiolitis can be successfully managed using home oxygen therapy. Aim: To report the impact of a Hospital in The Home Oxygen therapy program (HiTHOx) for selected infants and young children with acute bronchiolitis and other LRTI. Findings: The HiTHOx program appears to be a safe model of care for carefully selected infants and young children with acute bronchiolitis and LRTI that reduces the hospital length of stay. Conclusions: The HiTHOx program provides an alternative model of care for infants and young children with acute LRTI. Implementation of models of care similar to that of the HiTHOx program in other pediatric health services may have the potential to create additional bed capacity, at the time of year when it is most needed.